Preferential Market Access Design: Evidence and Lessons from African Apparel Exports to the US and the EU - de Melo, Jaime; Portugal-Perez, Alberto (World Bank, Washington, DC, 2013)
Least developed countries rely on preferential market access. Proof of sufficient transformation has to be provided to customs in importing countries by meeting Rules of Origin requirements to benefit from these preferences. These Rules of Origin have turned out to be complicated and burdensome for exporters in the least developed countries. Starting around 2001, under the United States Africa Growth Opportunity Act, 22 African countries exporting apparel to the United States can use fabric from any origin (single transformation) and still meet the criterion for preferential access (the so-called Special Rule), while the European Union continued to require yarn to be woven into fabric and then made into apparel in the same country (double transformation). This paper uses panel estimates over 1996-2004 to exploit this quasi-experimental change in the design of preferences. The paper estimates that this simplification contributed to an increase in export volume of about 168 percent for the top seven beneficiaries or approximately four times as much as the 44 percent growth effect from the initial preference access under the Africa Growth Opportunity Act without the single transformation. This change in design also mattered for diversity in apparel exports, as the number of export varieties grew more rapidly under the Africa Growth Opportunity Act special regime.